Epidemiological study on sarcoidosis in Moravia and Silesia - Kolek, V (Sarcoidosis, 1994)
Standard epidemiological and clinical features of sarcoidosis were evaluated in 24 regional centres from Moravia and Silesia (4 million inhabitants). During 1981-1990 the incidence ranged from 3.3 to 4.4/100,000 with slight decrease after 1985, when unselected chest X-ray screening was restricted. The prevalence (however disputable in sarcoidosis) increased from 41.3 to 63.1/100,000. Sex ratio male/female was 1: 2.35; only 39% of patients were younger than 40 years. Biopsy supported the diagnosis in 60% of cases. Tuberculin negativity was found in 64%. X-ray types were presented as follows: 0-2%, I-71%, II-22%, III-5%. Regional incidences varied from 0.9 to 11.7/100,000. Lower values were found in mining areas and high pneumoconiosis incidence. The course of the disease was benign with only sporadic extrapulmonary complications or pulmonary fibrosis. The results indicate that improved knowledge of sarcoidosis has brought epidemiological equilibrium to the evaluated area.
Keywords: Sarcoidosis; Humans; Sarcoidosis, Pulmonary; prevalence; Female; dospělí; lidé; sarkoidóza; Adult; ženské pohlaví; Male; Retrospective Studies; incidence; Incidence; Czech Republic; plicní sarkoidóza; Prevalence; retrospektivní studie; Česká republika; mužské pohlaví